Recyclable cement for low carbon concrete development - Thiri Thant Zin (Nanyang Technological University, 2023)
Ordinary Portland cement, which is commonly used in concrete, is associated with significant carbon dioxide (CO2) emissions during production. However, research suggests that Reactive Magnesium Oxide (MgO) cement (RMC) may offer a more environmentally friendly alternative due to its lower environmental impact and ability to sequence CO2 for strength development. This project seeks to further investigate the recyclability of RMC, particularly through the use of waste acid and alkaline. By developing sustainable construction technologies that reduce waste and minimize environmental impact, this research shall have important implications for promoting sustainable building practices.